1988
DOI: 10.1007/bf02142551
|View full text |Cite
|
Sign up to set email alerts
|

Histamine dependent cyclic AMP generating system in rabbit CNS: Interaction with neuroregulators and forskolin

Abstract: Histamine (HI) potently stimulated, through H2-receptors, cAMP accumulation in rabbit cerebral cortical slices but not in retinal pieces. The action of HI in the cerebral cortex was not significantly affected by dopamine, serotonin, melatonin and GABA-ergic drugs. Forskolin markedly stimulated cAMP accumulation both in the cerebral cortex and retina. There was a synergistic interaction between HI and forskolin in the cerebral cortex, whereas in the retina HI decreased the forskolin-activated cAMP accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Comparison of the HA action in the chick pineal, cerebral cortex, and retina revealed that the cyclic AMP-generating system of the pineal is much more sensitive to HA than these systems in the brain and retinal tissues (Nowak andSek, 1991, 1992;authors' unpublished data) . Like in guinea pig or rabbit brain (Daly, 1977 ;Daly et al ., 1982;Sek et al ., 1988 ;Nowak, 1993), the action of HA was strongly potentiated by forskolin, a direct activator of adenylyl cyclase (Seamon and Daly, 1986), suggesting a likely 134 3 receptor-type mode of action for HA. Furthermore, addition to the incubation medium of a phosphodiesterase inhibitor, IBMX, significantly increased the effect of HA, indicating that the HA action is related to the activation of cyclic AMP production rather than inhibition of the nucleotide breakdown .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the HA action in the chick pineal, cerebral cortex, and retina revealed that the cyclic AMP-generating system of the pineal is much more sensitive to HA than these systems in the brain and retinal tissues (Nowak andSek, 1991, 1992;authors' unpublished data) . Like in guinea pig or rabbit brain (Daly, 1977 ;Daly et al ., 1982;Sek et al ., 1988 ;Nowak, 1993), the action of HA was strongly potentiated by forskolin, a direct activator of adenylyl cyclase (Seamon and Daly, 1986), suggesting a likely 134 3 receptor-type mode of action for HA. Furthermore, addition to the incubation medium of a phosphodiesterase inhibitor, IBMX, significantly increased the effect of HA, indicating that the HA action is related to the activation of cyclic AMP production rather than inhibition of the nucleotide breakdown .…”
Section: Discussionmentioning
confidence: 99%
“…(c) It may suggest that the pineal HA receptors do not represent an H2 -type receptor ; the latter possibility, however, is in contrast to guinea pig hippocampus, where cyclic AMP production is linked to the activation of H2 receptors, and dimaprit, as expected, was active in this tissue (present study ; Palacios et al ., 1978). However, it must be noted that dimaprit (in contrast to HA) has been reported to be ineffective in enhancing cyclic AMP accumulation in chick cerebral cortex (Brine et al, 1983) and, surprisingly, in the CNS of rabbits (Al-Gadi and Hill, 1985), a species whose brain, similar to guinea pig brain (see, e.g., Daly, 1977;Palacios et al, 1978 ;Nowak et al, 1983), is known to possess HA HZ receptors linked to the cyclic AMPgenerating system (Al-Gadi and Hill, 1985 ;Sek et al, 1987Sek et al, , 1988Hill, 1990) . Thus, dimaprit, owing to its inconsistent, and thus unclarified, mode of action in at least some tissues/species (see Al-Gadi and Hill, 1985; see also Van der Goot et al, 1991), does not seem to be the drug of choice (as a pharmacological tool) in studying HA HZ receptors in the CNS .…”
Section: Discussionmentioning
confidence: 99%
“…1995a,b). Although the ineffectiveness of dimaprit could be attributed to its possible lack of intrinsic activity in some CNS tissues (as previously demonstrated for the rabbit brain and avian pineal gland; Al‐Gadi and Hill 1985; Sek et al . 1988; Nowak and Sek 1994; Nowak et al .…”
Section: Discussionmentioning
confidence: 75%
“…As in the rodent brain and the avian pineal gland (Daly et al . 1982; Sek et al . 1988; Nowak 1993; Nowak and Sek 1994), the action of HA was strongly potentiated by forskolin, a direct activator of adenylyl cyclase (Seamon and Daly 1986), suggesting a likely receptor‐related mode of action for HA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation